Surface Photovoltage Spectroscopy and AFM Analysis of CIGSe Thin Film Solar Cells - Nima E. Gorji; Ugo Reggiani; Leonardo Sandrolini (International Journal of Photoenergy)
The band gap, grain size, and topography of a Cu(In,Ga)Se2 (CIGSe) thin film solar cell are analyzed using surface photovoltage spectroscopy (SPV) and atomic force microscopy (AFM) techniques. From the steep increase in SPV signal the band gap of the CIGSe absorber, In2S3 and ZnO layers are extracted and found to be 1.1, 1.3 and 2.6 eV, respectively. Already below the band gap of ZnO layer, a slight SPV response at 1.40 eV photon energies is observed indicating the presence of deep donor states. The root mean square (rms) of the surface roughness is found to be 37.8 nm from AFM surface topography maps. The grain sizes are almost uniform and smaller than 1 μm.